Islamic And Conventional Economic Growth Thought Abū Yūsuf, Abū Ubaid, Al-Ghazāli, Ibn Khaldūn, Asy-Syatibi, Monzer Khaf, Adam Smith, David Ricardo, J.M. Keynes, Alfred Marshall, W.W. Rostow - Pujiono; Amalia, Euis; Haniatunnisa, Siti (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research discusses the thoughts on Islamic economic growth and conventional economics according to the figures, namely Abū Yūsuf, Abū Ubaid, Al-Ghazāli, Ibn Khaldūn, As-Syatibi, Monzer Khaf, Adam Smith, David Ricardo, J.M. Keynes, Alfred Marshall, and W.W. Rostow from a historical approach where his thoughts on the discourse of economic growth are quite a lot of references by researchers and academics of the world. The research method used in this article uses a literature review of the figure's work because what is discussed is a comparison of thoughts that have contributed to science through his works that have been used as references by subsequent generations. Based on the results and discussion of the thoughts of Islamic economic growth and conventional economics, it can be concluded that, in general, economists state that economic growth aims to achieve human prosperity by meeting the satisfaction needs of consuming goods and services. Meanwhile, according to Islamic figures, economic growth must refer to the basic principles of Sharia to achieve prosperity in the world and the hereafter (al-falāh). This study also discusses the concept of factors that affect economic growth.